A systematic review of prescription pattern monitoring studies and their effectiveness in promoting rational use of medicines - Jain, Shipra (Perspect Clin Res, 2015)
Prescription pattern monitoring studies (PPMS) are a tool for assessing the prescribing, dispensing and distribution of medicines. The main aim of PPMS is to facilitate rational use of medicines (RUM). There is paucity of published data analysing the effectiveness of PPMS. The present review has been done to assess the effectiveness of prescription pattern monitoring studies in promoting RUM. Data search was conducted on internet. A multitude of PPMS done on different classes of drugs were collected and analyzed. PPMS using WHO prescribing indicators were also included. The present article reviews various prescription pattern monitoring studies of drugs conducted all over country and abroad. It was observed in the majority of such studies that physicians do not adhere to the guidelines made by regulatory agencies leading to irrational use of medicines. This in turn leads to increased incidence of treatment failure, antimicrobial resistance and economic burden on the patient and the community as a whole. The treatment of diseases by the use of essential drugs, prescribed by their generic names, has been emphasized by the WHO and the National Health Policy of India. We conclude that the prescription monitoring studies provide a bridge between areas like rational use of drugs, pharmacovigilance, evidence based medicine, pharmacoeconomics, pharmacogenetics and ecopharmacovigilance. In India, this is the need of the hour to utilise the data generated by so many prescription pattern monitoring studies done in every state and on every drug, so that the main aim of promoting rational use of drugs is fulfilled.